Brain functional abnormality in drug treated and drug naïve adolescents with borderline personality disorder: Evidence for default mode network dysfunction. (May 2023) - Salgado-Pineda, Pilar; Ferrer, Marc; Calvo, Natàlia; Costa, Xavier; Ribas, Núria; Lara, Benjamín; Tarragona, Brenda; Fuentes-Claramonte, Paola; Salvador, Raymond; Pomarol-Clotet, Edith
Abstract: Background: Patients with borderline personality disorder (BPD) have been found to show functional brain abnormality, including in the medial frontal cortex and other areas of the default mode network (DMN). The current study aimed to examine activations and de-activations in drug treated and medication-free female adolescents with the disorder. Methods: 39 DSM-5 adolescent female patients with BPD without psychiatric comorbidity and 31 matched healthy female adolescents underwent fMRI during the performance of 1-back and 2-back versions of the n-back working memory task. Linear models were used to obtain maps of within-group activations and de-activations and areas of differences between the groups. Results: On corrected whole-brain analysis, the BPD patients showed failure to de-activate a region of the medial frontal cortex in the 2-back > 1-back comparison. The 30 never-medicated patients additionally showed a failure to de-activate the right hippocampus in the 2-back versus baseline contrast. Conclusions: Evidence of DMN dysfunction was observed in adolescent patients with BPD. Because the relevant medial frontal and hippocampal changes were seen in unmedicated young patients without comorbidity, they might be considered intrinsic to the disorder.